1978
DOI: 10.1177/002221947801100104
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities and the Vestibular System

Abstract: Though "learning disabilities" is recognized to be an umbrella term for a collection of diverse disorders, research studies too frequently treat the LD group as homogeneous, comparing its functioning with that of a normal control group. This study examines a subpopulation of LD youngsters, those with disorders in the vestibular system which responds to gravity and changes in one's rate of movement. While the outcomes themselves are interesting, the structure of the research approach has distinct advantages ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 9 publications
3
69
1
1
Order By: Relevance
“…Comparable results were described by Hirabayashi and Iwasaki (1995), who considered hyperactivity to be a responsible factor for maturational slowness in posture control seen in young males. Ayres (1978) found that the sensory system is not only important for balance control but also for higher central nervous functions, like attention and cognition, in conjunction with the vestibular system. Hirabayashi and Iwasaki supposed that delayed vestibular development could play a significant role in children with attention-deficit-hyperactivity disorder.…”
Section: Differences In Standing Stability In Relation To Sexmentioning
confidence: 99%
“…Comparable results were described by Hirabayashi and Iwasaki (1995), who considered hyperactivity to be a responsible factor for maturational slowness in posture control seen in young males. Ayres (1978) found that the sensory system is not only important for balance control but also for higher central nervous functions, like attention and cognition, in conjunction with the vestibular system. Hirabayashi and Iwasaki supposed that delayed vestibular development could play a significant role in children with attention-deficit-hyperactivity disorder.…”
Section: Differences In Standing Stability In Relation To Sexmentioning
confidence: 99%
“…All university students were approved in the final evaluation. The academic performance of students with or without vertigo or other kinds of dizziness and/or imbalance when walking was similar, in contrast to what was reported in children [8][9][10] . It was possible to assume that the university students reached a developmental phase in which neurotological disorders do not interfere with learning.…”
Section: Discussionmentioning
confidence: 51%
“…These children may position the head in an unusual way when writing, may experience spatial disorientation or distorted sensations of size and the body weight and can cause inability of practicing some physical exercises 7 . Vertigo and other kinds of dizziness of vestibular origin may interfere in the psychological behavior and school performance as well [8][9][10] . Vestibular dysfunction in childhood may significantly affect communication; low academic performance can be a valuable index of possible labyrinthopathy 10 .…”
mentioning
confidence: 99%
“…Early therapies included treatment with anti-motion sickness medication (Levinson, 1991) as well as specific motion stimulation (e.g. Silver, 1986) and combined multisensory integration therapies (Ayres, 1978). Yet, these findings were already at that time heavily debated and even considered wrong (see Pope and Whiteley, 2003;Silver, 1986 for reviews), and have largely lost their influence on current models of dyslexia.…”
Section: Vestibular Stimulation In Neurodevelopmental Disordersmentioning
confidence: 99%